DINAMIKA POPULASI DAN KERUSAKAN POHON TEMPAT BERTENGGER KALONG (PTEROPUS VAMPYRUS) DI KEBUN RAYA BOGOR - Soegiharto, Sri; Kartono, Agus P.; Maryanto, Ibnu (JURNAL BIOLOGI INDONESIA, 2019)
ABSTRACTThe study on population dynamic and  roosting trees damage by flying fox was conducted for 16 months (March 2008-June 2009) in Bogor Botanical Garden.  Recording of individual flying fox was carried out by use direct observation in the roosting trees habitat at 9.00-15.00, with one replication every week. The result indicated that in 2008 the total flying fox were 420 individuals and in 2009 were 563 individuals (160 juveniles, 218 adult females and 185 adult males). The natality and mortality rate in this location is 0.0214 and 0.0099 respectively. The flying fox population growth can be predicted using exponential equation is N(t+1)=563(1.8395)t.  The study also indicated that in the KRB there are 9 individual trees which are the main perch, 2 individual trees of Pterodotus alata, Pterocarpus indicus, and Shorea leprosula, and each 1 individual tree of the species  Dipterocarpus cornutus, Ficus drupacea, and Syzygium syzygioides. The extent of damage to the tree where the perch is very dependent on the diameter of the canopy, bat population size in one tree, and time periods per roosting season.  Keywords: Population Dynamic, Flying Fox (Pteropus vampyrus), Bogor Botanical Garden